Answer :

amna04352

Answer:

u1 = 1

u6 = 31

un = 1 + 6(n - 1)

Step-by-step explanation:

Sn = 3n² - 2n

u1 = S1

3(1)² - 2(1)

3 - 2

1

u6 = S6 - S5

[3(6)² - 2(6)] - [3(5)² - 2(5)]

96 - 65

31

un = a + (n - 1)d

u6 = a + 5d

31 = 1 + 5d

5d = 30

d = 6

un = 1 + 6(n - 1)

Step-by-step explanation:

Step 1:  Find [tex]u_1[/tex]

[tex]u_1=u_1-u_0[/tex]

[tex]u_1 = 3(1)^2-2(1) - (3(0)^2-2(0))[/tex]

[tex]u_1 = 3(1) - 2 - (0)[/tex]

[tex]u_1=3-2[/tex]

[tex]u_1 = 1[/tex]

Answer:  [tex]u_1 = 1[/tex]

Step 2:  Find [tex]u_6[/tex]

[tex]u_6 = u_6-u_5[/tex]

[tex]u_6=(3(6)^2-2(6))-(3(5)^2-2(5))[/tex]

[tex]u_6=(3(36)-12)-(3(25)-10)[/tex]

[tex]u_6 = (108-12) - (75-10)[/tex]

[tex]u_6=96 - 65[/tex]

[tex]u_6=31[/tex]

Answer:  [tex]u_6=31[/tex]

Other Questions